GENERATING ELECTRICITY WITH NATURAL GAS: IT'S PLENTIFUL AND CHEAP, BUT REGULATION IS NEEDED TO PREVENT ENVIRONMENTAL DEGRADATION (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
Natural gas is plentiful and cheap, and is expected to remain so. Therefore, it is likely to continue as a prominent fuel choice for generating electrical power until about 2035 to 2050. However, there are environmental issues associated with the production of natural gas and its subsequent combustion for generating electricity, including, but not limited to, the production of greenhouse gases that contribute to climate change. These environmental issues must be addressed if natural gas is to be viewed as desirable for generating electricity. In this analysis, I will first briefly consider the supply of natural gas, its cost, and the role it will play in generating electricity. I will then consider whether renewable sources of energy (“renewables”) will eventually comprise a significant fraction of electrical power generation. I will also discuss the contribution to climate change of electricity generated from coal, renewables, and natural gas. After that, I will address whether natural gas will be a “bridge fuel” to a more carbon-neutral system of electricity generation. Then, I will turn to the primary issue considered in this analysis—the environmental impacts of natural gas used to generate electricity, including impacts on climate change, water quality, air quality, land uses, wildlife, and local communities. In the last section, I will argue that the initial primary area of emphasis for electricity generation should be increased energy use efficiency—a clean, fast, and inexpensive path that can avoid problems associated with any fuel used to generate electrical power.